ELECTRONIC BANKING-MARKETING AND ITS IMPACT ON ENHANCING ATTRACT CUSTOMERS A CASE STUDY OF THE RAFIDAIN BANK IN DHI QAR GOVERNORATE - Sattar Awad Dhmaid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to study the importance of electronic banking marketing and its role in enhancing attract customers at Al-Rafidain Bank in Dhi Qar Governorate, southern Iraq, as this bank was chosen as a field of application based on a hypothetical scheme that takes into consideration the direction of the relationship between electronic banking marketing and enhancing attracting customer. A random sample of managers working in the bank was selected as a sample for research, with (50) members of departments and division directors in all branches of the Rafidain Bank in Dhi Qar Governorate, the questionnaire was adopted as the main tool for collecting research data. In order to analyze the research data, the statistical program statistical package of social sciences (SPSS) was used, and the most important statistical tools adopted in the analysis are (frequency percentage, arithmetic mean, standard deviation, coefficient of variation, correlation coefficient, and simple linear regression). The research concluded with the most important conclusions, including the lack of diversification of digital banking services at the Rafidain Bank, Dhi Qar Branch, as well as the lack of adopting modern technology in most departments and divisions of the bank, which reflected negatively on the provision of digital banking services in terms of speed, accuracy, and cost. Furthermore, the research achieved a set of proposals, the most important of which is the increase in interest in research and development, creation of efficient electronic banking marketing channels. As well as, the development of mechanisms for electronic evaluation and follow-up in order to help customers adapt and respond to the modern electronic structure and know their satisfaction with the services provided.